PENGARUH KONSENTRASI DAN LAMA PERENDAMAN EKSTRAK RUMPUT LAUT TERHADAP PERKECAMBAHAN DAN PERTUMBUHAN VEGETATIF BENIH PADI - Wibowo, Galuh Akmal Yudistira; Triani, Nova; Moeljani , Ida Retno (JURNAL AGROTROPIKA, 2025)
The growth and production of paddy plants is influenced in the early growth phase during germination and vegetative growth. The aim of this research was to determine the effect of concentration and soaking duration of seaweed extract on the germination and growth of rice seeds. This research was carried out in April-May 2024 at UPT. PSBTPH East Java. Treatments were arranged factorial (4x3) using a Completely Randomized Design with 3 replications. Factor I is the concentration of seaweed extract (2 ml.l-1, 4 ml.l-1, 6 ml.l-1 and 8 ml.l-1). Factor II is the duration of soaking (12 hours, 24 hours dan 36 hours). Observation variables included germination capacity, maximum growth potential, wet weight of sprouts, dry weight of sprouts, coleoptile length, root length of seedlings, number of seedling leaves, height of seedlings, and total weight of seedlings. The results showed that the interaction between concentration and soaking time of seaweed extract had a real influence on the length of the seedling and the number of seedling leaves. Key words: Biostimulant, nursery, rice, seeds